Survival estimates for the Australian sea lion: Negative correlation of sea surface temperature with cohort survival to weaning. Issue 1 (21st May 2012) - McIntosh, Rebecca R.; Arthur, Anthony D.; Dennis, Terry; Berris, Mel; Goldsworthy, Simon D.; Shaughnessy, Peter D.; Teixeira, Carlos E. P.
Abstract The Australian sea lion (Neophoca cinerea) population at Seal Bay Conservation Park, South Australia, is estimated to be declining at a rate of 1.14% per breeding season. To better understand the potential causes of this decline, survival rates were examined to 14 yr of age for eight cohorts marked as pups (aged 0.17 yr) between 1991 and 2002. Apparent yearly survival rates (Φ) varied by cohort for pups from marking to weaning at 1.5 yr (Φ= 0.30–0.67). Postweaning juvenile survival (1.5–3 yr) was 0.89 and survival from 3 to 14 yr was constant (Φ female:male = 0.96:0.89). Φ of pup cohorts was negatively correlated to local sea surface temperature where the sea lions forage (SST) and was especially low for cohort 7 in 2000 (0.30). It is possible that periods of unusually warm oceanographic conditions may be limiting primary production and inhibiting maternal provisioning to pups. Pup survival to weaning is relatively low compared to other otariid species, is likely to limit recruitment, and may be contributing to the decline in pup abundance observed in the colony.